In vivo pharmacokinetic and pharmacodynamic study and cutoff of florfenicol against Riemerella anatipestifer in ducks - Hui-Lin Zhang; Fa-Lei Li; Hui-Yang Chen; Ding-Mei Qin; Shu-Jun Sun; Meng-Meng Zhang; Huan-Zhong Ding; Yong Liu (Poultry Science)
Riemerella anatipestifer causes serious infections, characterized by septicemia and serositis, in ducks and geese. R. anatipestifer is mainly controlled through antimicrobial chemotherapy. This study investigated the pharmacokinetic/pharmacodynamic (PK/PD) integration of florfenicol (FF) against R. anatipestifer by establishing a systemic infection model in ducks. For PK studies, FF was administrated intramuscularly (i.m.) at single doses of 2.5, 10, 20, and 40 mg/kg body weight. The concentrations of FF in blood, lung, and liver were determined. FF was rapidly eliminated in R. anatipestifer-infected ducks with T1/2kel values of 1.67, 2.2, and 1.62 h in the plasma, lung, and liver, respectively. For PD analysis, the infected ducks were administered FF via the i.m. route at doses of 5–80 mg/kg body weight, using 2 dosing regimens involving the administration of FF either once or twice over 24 h. The bacteria were counted 24 h after drug administration. Bactericidal effects in tissues (including those of the heart, liver, spleen, lung, kidney, and brain) were achieved at doses of ≥20 mg/kg following 2 i.m. injections of FF within 24 h. The data obtained were fitted to a sigmoidal Emax model. The results demonstrated that AUC24h/minimum inhibitory concentration (MIC) (R2 = 0.930) and Cmax/MIC (R2 = 0.930) were the optimal PK/PD parameters for describing the antibacterial activity of FF. The magnitudes of AUC24h/MIC and Cmax/MIC required to produce a drop of 3 Log10CFU/mL in the bacterial count were 58.56 h and 15.10, respectively. The MIC distribution of 164 R. anatipestifer strains for FF ranged from 0.25 to 16 μg/mL. Both the values of COWT derived from the ECOFFinder program and the COPD based on a 10,000-subject Monte Carlo simulation of FF against R. anatipestifer were 1 μg/mL, confirming that infections caused by strains with MIC ≤ 1 μg/mL could be effectively treated. Our study results may prove useful in optimizing FF regimens to treat R. anatipestifer infections.